1969
DOI: 10.2135/cropsci1969.0011183x000900050006x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Selection Based on Yield of Topcross Progenies and of S2 Progenies in Maize (Zea mays L.)1

Abstract: Three methods of breeding for higher grain yield in maize (Zea mays L.) were compared: (a) recurrent selection for combining ability with the parental population (Parental Tester method), (b) recurrent selection for combining ability with an unrelated inbred line (Inbred Tester method), and (c) recurrent selection for yield of S2 progenies per se (S2 Progeny method).After three cycles of selection for grain yield had been completed with each of the three methods, the nine resulting selected populations were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Beyond the numerical predictions of selection response we have presented, a better understanding of the underlying genetic principles in maize populations that limit the relationship between inbred and outbred performance is needed to determine if the relationship can be manipulated. Previous authors who proposed that inbred‐progeny recurrent selection would effectively improve outbred population performance generally assumed a single locus genetic model with partial or complete dominance (Eberhart, 1970; Comstock, 1964; Horner et al, 1969; Cockerham and Matzinger, 1985). However, overdominance, epistasis, and or linkage disequilibrium could all change these predictions profoundly, as could other possible genetic phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beyond the numerical predictions of selection response we have presented, a better understanding of the underlying genetic principles in maize populations that limit the relationship between inbred and outbred performance is needed to determine if the relationship can be manipulated. Previous authors who proposed that inbred‐progeny recurrent selection would effectively improve outbred population performance generally assumed a single locus genetic model with partial or complete dominance (Eberhart, 1970; Comstock, 1964; Horner et al, 1969; Cockerham and Matzinger, 1985). However, overdominance, epistasis, and or linkage disequilibrium could all change these predictions profoundly, as could other possible genetic phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…I nbred‐progeny recurrent selection was shown to be a superior method to mass selection and half‐sib recurrent selection based on theoretical arguments by numerous authors over an approximately 20‐yr period (Comstock, 1964;Horner et al, 1969; Eberhart, 1970;Choo and Kannenberg, 1979;Wricke, 1976;Wright, 1980;Cockerham and Matzinger, 1985). In contrast to theoretical predictions, inbred‐progeny selection has not been demonstrated to be universally superior based on empirical work (Lamkey, 1992; Coors, 1999) nor has it been widely adopted in industrial maize ( Zea mays L.) breeding programs, where the vast majority of performance evaluations have been based on testcross performance for decades (Hallauer et al, 1988).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…M any theoretical comparisons among selection methods have shown that inbred‐progeny recurrent selection methods are expected to be much more effective than mass selection or half‐sib selection with either related or unrelated testers (Comstock, 1964; Horner et al, 1969; Eberhart, 1970; Choo and Kannenberg, 1979; Wricke, 1976; Wright, 1980; Cockerham and Matzinger, 1985). Such theoretical comparisons were generally based on single locus models that did not include overdominance (Comstock, 1964; Horner et al, 1969; Eberhart, 1970; Choo and Kannenberg, 1979; Wricke, 1976). However, addition of epistasis in two cases did not change the general conclusion that inbred‐progeny selection was predicted to be a superior method of population improvement (Wright, 1980; Cockerham and Matzinger, 1985).…”
mentioning
confidence: 99%